Flame-Retardant Efficiency of Oligomeric Flame Retardants of the New Generation - Nurkulov, F. N.; Sitdikov, I. I.; Akhmedov, S. I. (European Journal of Life Safety and Stability (2660-9630), 2022)
Phosphorous, silicon- and nitrogen-containing oligomeric flame retardants of the AJ-13 brand were obtained in the article, optimal compositions of oligomeric flame retardants with synergetic properties for the processing of wood materials were determined and their flame retardant properties based on GOST were studied. Based on the results of experimental tests, it was found that the flame retardant composition of the AJ-13 brand provides the I group of fire-protective effectiveness of wood materials